Optimization of transverse modes in a vertical-cavity surface-emitting semiconductor laser with optical feedback and pump noise - Araullo, Alessandra P.
We aim to achieve beam optimization in a large aperture vertical-cavity surface-emitting laser (VCSEL), which generally operates in multiple transverse modes at high injection currents well above threshold. We show the use of a spatiotemporal VCSEL model in the simulation of the transverse laser modes; the model is based on two-dimensional (2-D) rate equations which allow the computation of dynamic gain competition resulting from inhomogeneous field and carrier spatial distributions in the cavity. We find that in general, feedback is able to minimize the energy distribution to a few active modes in the VCSEL. For the 6µm, low level optical feedback at pumping currents slightly above and up to 3 times the threshold is more effective than strong feedback in achieving a more optimized state for the multimode VCSEL. A phase-locking phenomenon is observed at the 15-30 percent feedback range for the VCSEL operating at up to twice the threshold current, indicative of synchronization among the cavity modes in the system. The optimzation achieved through feedback is robust to the addition of pump noise up to 300 percent of the threshold current.
Computer print out.
Keywords: Beamed-energy propulsion; Semiconductor lasers